Post-migration food habits of New Zealand South Asian migrants: Implications for health promotion practice - Sherly Parackal (Elsevier, 2023)
Introduction: South Asian migrants in western countries have a high risk for diet related diseases post-migration. Hence knowledge on food habits that change post-migration, which are detrimental to health, are critical for health promotion initiatives to reduce this disease burden. Objective: to describe food consumption changes post-migration according to sex and duration of residence in New Zealand among South Asian migrants. Methods: A cross-sectional mail survey of 150 self-selected people of South Asian ethnicity aged 25-59 years in New Zealand. Results: The study achieved responses from 112 participants (75%) with a mean age of 36 (7.5) years. Consumption of green leafy vegetables reduced post-migration for females and in new migrants (P < 0.05). Fruit consumption increased in both genders and across duration of residence (P < 0.05). Only 15% of males and 36% of females met the 3 + a day recommendation for vegetable consumption. Consumption of traditional breads, breakfast items and rice (males) decreased whilst that of breakfast cereals increased (P < 0.05). Consumption of low-fat milk, cheese, ice-cream, butter (females) and margarine increased, whilst ghee decreased (P < 0.05). Consumption of fish, lentils, traditional sweets and savouries decreased, whilst meat, processed meat, chicken, potato chips, cakes and pastries (females) and alcohol (males) increased (P < 0.05), post-migration. Thirty-three percent of males and 24% of females consumed takeaways "weekly or more often", with the majority (male: 51%; female: 36%) consuming European foods such as pizzas and pastas. Thirteen percent of males and 26% of females consumed festival foods "weekly or more often." More than half the participants were obese with BMI increasing with duration of residence (P = 0.025). Conclusions: A food-based health promotion initiative focused on inadequate consumption of fruits and vegetables, increased consumption of dairy foods such as cheese and ice cream, and high fat European takeaway foods would be warranted particularly in new South Asian migrants.